Chinese Experiences and Lessons Learnt in Agricultural Development Since 1949 - M. A, Bin Jiang; Herman , Joost; Zhao, Yongjun (Asian Journal of Agriculture and Rural Development, 2017)
The Chinese agricultural development has made remarkable achievements, especially in recent four decades, while as several issues also emerged at the same time. This paper uses a historical view to find out the facts that exist in the agricultural development experiences in China since the People’s Republic of China founded in 1949, both achievements and major issues. In this paper, the Chinese development experiences have been divided into three phases in accordance with the developmental characteristics in each stage, and then to search for the main achievements in the past decades and problems that need to solve currently.